Oral administration of non‐absorbable delayed release 6‐mercaptopurine is locally active in the gut, exerts a systemic immune effect and alleviates Crohn's disease with low rate of side effects: results of double blind Phase II clinical trial. (August 2015) - Israeli, E.; Goldin, E.; Fishman, S.; Konikoff, F.; Lavy, A.; Chowers, Y.; Melzer, E.; Lahat, A.; Mahamid, M.; Shirin, H.; Nussinson, E.; Segol, O.; et al.
Summary Therapy for Crohn's disease (CD) with thiopurines is limited by systemic side effects. A novel formulation of fixed‐dose, delayed‐release 6‐mercaptopurine (DR‐6MP) was developed, with local effect on the gut immune system and minimal absorption. The aim of this study was to evaluate the safety and efficacy of DR‐6MP in patients with moderately severe CD compared to systemically delivered 6‐mercaptopurine (Purinethol). Seventy CD patients were enrolled into a 12‐week, double‐blind controlled trial. The primary end‐point was the percentage of subjects with clinical remission [Crohn's Disease Activity Index (CDAI) < 150] or clinical response (100‐point CDAI reduction). Twenty‐six (56·5%) and 13 (54·2%) subjects from the DR‐6MP and Purinethol cohorts, respectively, completed the study. DR‐6MP had similar efficacy to Purinethol following 12 weeks of treatment. However, the time to maximal clinical response was 8 weeks for DR‐6MP versus 12 weeks for Purinethol. A higher proportion of patients on DR‐6MP showed clinical remission at week 8. A greater improvement in Inflammatory Bowel Disease Questionnaire (IBDQ) score was noted in the DR‐6MP group. DR‐6MP led to a decrease of CD62+ expression on T cells, implying a reduction of lymphocyte adhesion to site of inflammation. DR‐6MP was safer than Purinethol, with significantly fewer adverse events (AEs). There was no evidence of drug‐induced leucopenia in the DR‐6MP group; the proportion of subjects who developed hepatotoxicity was lower for the DR‐6MP. Non‐absorbable DR‐6MP is safe and biologically active in the gut. It is clinically effective, exerting a systemic immune response with low systemic bioavailability and a low incidence of side effects.